Respuesta :

Answer:

x = -5, 2

Step-by-step explanation:

The first step to factor the equation is removing any factors/like terms that all of the variables share.

In the equation [tex]y = 2x^2+6x-20[/tex], all numbers are multiples of 2, therefore you can factor out 2 from to equation

[tex]y = 2(\frac{2x^2}{2} + \frac{6x}{2} -\frac{20}{2})[/tex]

[tex]y = 2(x^2+3x-10)[/tex]

Next, you can factor the equation in the parenthesis. Since x^2 is not multiplied by anything, you know that the factors of x^2 must be x and x. Therefore, the two factors of -10 must add up to 3. The only two factors of -10/x that add up to 3 are 5 * -2.

The factors of the equation are then (2)(x+5)(x-2)

Lastly, set up only the factors containing a x to 0 in order to solve for x-intercept.

x+5 = 0; x= 0-5 ; x = -5

x - 2 = 0; x = 0 + 2; x = 2